(untitled) (Swarnadwar, 2025)
The central Himalaya, including Nepal and its adjoining region, is a seismically active region, and is seismically catagorized in to three zones. One of this zone is the western region of Nepal. This study examine the spatial and temporal variation of seismicity in Western Nepal, provides how the activity was changing during the period 1964-2008. Using earthquake data from NEIC and ISC catalogs, a comprehensive data set is prepared for the study period. This analysis focus on the spatial, temporal, and depth-wise distribution of earthquakes in the region. The clustering pattern of the shallow and intermediate events extending beyond 70 km focal depth in the western part of the central himalayan thrusts signify a high crustal thickness.